Shaping Striated Muscles with Ubiquitin Proteasome System in Health and Disease. Issue 9 (September 2019) - Hnia, Karim; Clausen, Tim; Moog-Lutz, Christel
Abstract : For long-lived contractile cells, such as striated muscle cells, maintaining proteome integrity is a challenging task. These cells require hundreds of components that must be properly synthesized, folded, and incorporated into the basic contractile unit, the sarcomere. Muscle protein quality control in cells is mainly guaranteed by the ubiquitin-proteasome system (UPS), the lysosome-autophagy system, and various molecular chaperones. Recent studies establish the concept of dedicated UPS in the regulation of sarcomere assembly during development and in adult life to maintain the intricate and interwoven organization of protein complexes in muscle. Failure of sarcomere protein quality control often represents the basis of severe myopathies and cardiomyopathies in human, further highlighting its importance in producing and maintaining the contractile machinery of muscle cells in shape. Highlights: A protein quality control (PQC) network ensures the maintenance and adaptation of the contractile unit, the sarcomere, in response to physiological stimuli and under stress conditions. The ubiquitin-proteasome system (UPS) is the main player in the PQC network and controls specific sarcomere element degradation, supporting the concept of specialized and dedicated protein turnover machinery. As with other UPS components, ubiquitin ligases act in a highly selective and timely controlled way to ensure the building, maintenance, and adaptation of sarcomeres at all stages of muscle lifespan. The interplay between PQC actors (UPS, chaperones, and autophagy) supports a fine-tuning regulation of the sarcomere quality control. The development of proteasome inhibitors and the discovery of small molecules targeting the UPS pave the way for future innovative therapy in striated muscle diseases.